Beyond The Classroom: The Google Mindset - Kansas State University, K-State First (Kansas State University. K-State First., 2016)
A poster promoting the presentation "The Google Mindset" at Kansas State University, hosted by Ashley Rhodes, Associate Professor of Biology on February 17, 2016 at 7-8 PM, in Putnam Hall.
Keywords: Beyond The Classroom; Events; Engagement; Community building; Application of learning; Google; Posters